A flexible biomimetic skin polyurethane condom, preparation method and application

CN122917271APending Publication Date: 2026-10-16浙江睿博零零壹高分子有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611379490.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]但是,在仿生材料方面,聚氨酯避孕套虽可实现更薄的厚度,具备良好的阻隔性能与导热性能,且不含乳胶蛋白、无致敏风险,但其弹性与柔软性不足、体感偏硬,薄膜表面光滑均一、缺乏人体皮肤特有的纹理与微起伏特征,使用时存在明显的塑料感与隔膜感,贴合度及触觉真实感难以达到仿生要求,有待改进

Benefits of technology

1、通过采用聚轮烷多元醇构建滑环交联结构,并引入含光/力响应性基团的辅助扩链剂形成牺牲键网络,使基膜层在低应变区具有柔软触感,并在高应变区应变硬化而提供可靠力学性能的效果;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a flexible bionic skin polyurethane condom, a preparation method and application, relates to the technical field of bionic materials, and comprises the following steps: step 1, prepolymerization: polyisocyanate is reacted with polyrotaxane polyol and polymer polyol at a temperature of 70-90 DEG C for 2-4 h to obtain an NCO-terminated prepolymer; step 2, chain extension and dispersion: the NCO-terminated prepolymer is taken and hydrophilic chain extenders and auxiliary chain extenders are added, chain extension reaction is carried out at a temperature of 50-70 DEG C for 0.5-1.5 h, and then water is added for emulsion dispersion to obtain water-based polyurethane latex; step 3, dip forming: a mold is immersed in the water-based polyurethane latex, and a base film layer is formed through multiple dipping, interlayer drying and curing; step 4, post-treatment: through demolding and cleaning treatment, the flexible bionic skin polyurethane condom is obtained. The application has the effects of realizing soft touch, good fit and reliable mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of biomimetic materials technology, and in particular to a flexible biomimetic polyurethane condom, its preparation method, and its application. Background Technology

[0002] Condoms are thin-film products that serve both contraceptive and sexually transmitted disease prevention functions. Their barrier properties, mechanical strength, and user experience directly affect their protective efficacy and user acceptance. With increasing health awareness, users' requirements for condoms have expanded beyond simple strength and barrier properties to include tactile feel, softness, fit, and thermal conductivity, with a desire for condom films to closely resemble the feel of human skin. To this end, condom materials have evolved from natural latex to polymers such as polyurethane. In recent years, the concept of biomimetic skin has been introduced into this field. This involves using molecular design and surface structure control to mimic the tactile sensation of human skin in condom films, and has become an important research direction in this area.

[0003] In the technical route of raw material composition of polymer materials such as polyurethane, polyether-type or polyester-type thermoplastic polyurethane is used as the base material. During preparation, polyurethane granules are dissolved in organic solvents to prepare impregnation liquid, or water-based polyurethane emulsion is used with chain extenders, lubricants, antioxidants and other additives to prepare latex. The latex is then produced through processes such as solution or emulsion preparation, impregnation molding, drying and demolding.

[0004] However, in terms of biomimetic materials, although polyurethane condoms can achieve a thinner thickness, have good barrier and thermal conductivity, and are free of latex protein and have no risk of allergies, they lack elasticity and softness, feel rather hard, and have a smooth and uniform film surface that lacks the unique texture and micro-undulations of human skin. When used, they have a noticeable plastic feel and a barrier feeling, and the fit and tactile realism are difficult to meet the requirements of biomimetic design and need to be improved. Summary of the Invention

[0005] In view of this, the first objective of this application is to provide a method for preparing a flexible biomimetic polyurethane condom, so as to achieve a soft touch, good fit, and reliable mechanical properties. The specific solution is as follows: A method for preparing a flexible biomimetic polyurethane condom includes the following steps: Step 1, Prepolymerization reaction: Polyisocyanate, polyrotaxane polyol, and polymer polyol are prepolymerized at 70-90℃ for 2-4 hours to obtain NCO-terminated prepolymer; Step 2, chain extension and dispersion: Take the NCO-terminated prepolymer and add a hydrophilic chain extender and an auxiliary chain extender. Control the temperature at 50-70℃ and carry out the chain extension reaction for 0.5-1.5 hours. Then add water to emulsify and disperse to obtain waterborne polyurethane latex. Step 3, Impregnation molding: The mold is immersed in water-based polyurethane latex, and after multiple impregnations, interlayer drying and curing, a base film layer is formed; Step 4, Post-processing: After demolding and cleaning, the finished flexible bionic polyurethane condom is obtained. in: Based on the molar amount of NCO, the amount of the polyrotaxane polyol is 10-35%, the amount of the polymer polyol is 20-50%, the amount of the hydrophilic chain extender is 5-15%, and the amount of the auxiliary chain extender is 1-8%. The hydrophilic chain extender is a hydrophilic chain extender containing a carboxyl group; the auxiliary chain extender is an auxiliary chain extender containing a photo / mechanical responsive group.

[0006] Preferably, in step 1, the polyrotaxane polyol is obtained by inclusion reaction of polyethylene glycol aqueous solution and α-cyclodextrin followed by end-capping with an end-capping agent; the concentration of the polyethylene glycol aqueous solution is 5-15 wt%; the molar ratio of α-cyclodextrin to polyethylene glycol is (5-30):1; the temperature of the inclusion reaction is 60-80℃, and the inclusion time is 2-6 h; the molar ratio of the end-capping agent to the terminal hydroxyl group of the polyethylene glycol is (2-3):1, and the end-capping reaction temperature is controlled at 25-50℃, and the end-capping reaction time is 12-24 h; the end-capping agent is at least one of adamantane, triphenylmethyl isocyanate, or pyrene isocyanate; the prepolymerization reaction is added with a catalyst accounting for 0.01-0.1% of the total mass, and the catalyst is an organobismuth catalyst or an organotin catalyst.

[0007] Preferably, in step 2, triethylamine and / or triethanolamine are added for neutralization before emulsification and dispersion, and the degree of neutralization is controlled to be 70-100%; the solid content of the waterborne polyurethane latex is 25-45%.

[0008] Preferably, in step 3, the impregnation speed is 1-5 mm / s, the single impregnation time is 10-60 s, and the impregnation is repeated 2-5 times; the interlayer drying temperature is 40-70℃, and the time is 3-10 min; the curing temperature is 70-90℃, and the time is 10-30 min.

[0009] Preferably, in step 3, the base film layer undergoes surface treatment to obtain a dense film layer; the surface treatment involves immersing the base film layer in a surface slurry and drying it to form a hydrophilic and dense surface layer; the immersion rate of the surface treatment is 0.5-3 mm / s, and the immersion time is 5-30 s; the drying temperature is 40-60℃, and the drying time is 3-8 min; and the thickness of the hydrophilic and dense surface layer is controlled to be 2-10 μm.

[0010] Preferably, the surface slurry has a solid content of 10-30% and includes 5-20% by mass of isocyanate-terminated prepolymer, 0.5-3% of a moisturizing and lubricating component, and the balance being a hydrophilic segment; the isocyanate-terminated prepolymer is prepared from at least one of polyisocyanate and polyether polyol and polyester polyol, and has an NCO content of 3-12 wt% and a number average molecular weight of 500-3000; the moisturizing and lubricating component is at least one of hyaluronic acid, polyethylene glycol, and chitosan; the hydrophilic segment is a polyethylene oxide segment and has a number average molecular weight of 400-2000.

[0011] Preferably: the dense film-forming layer is subjected to ion crosslinking treatment to obtain a composite base film layer; the ion crosslinking treatment includes immersing the dense film-forming layer in a crosslinking solution containing multivalent metal ions for crosslinking impregnation treatment; the multivalent metal ions include Ca 2+ Zn 2+ Or Al 3+ At least one of the following: the crosslinking solution is at least one of calcium chloride aqueous solution, zinc acetate aqueous solution or aluminum chloride aqueous solution; the mass concentration of the crosslinking solution is 1-10%, and the crosslinking immersion treatment time is controlled to be 30-300s, and the immersion temperature is 20-40℃.

[0012] Preferably, the auxiliary chain extender is a chain extender containing a spiropyran structure or a photo / mechanical responsive molecule containing a diarylethylene structure.

[0013] The second objective of this application is to provide a flexible biomimetic polyurethane condom, which is prepared by the method described above. The flexible biomimetic polyurethane condom includes a base film layer and a hydrophilic dense surface layer disposed on the outer surface of the base film layer.

[0014] A third objective of this application is to provide an application of a flexible biomimetic polyurethane condom, including the use of a flexible biomimetic polyurethane condom as described above, and its application in contraception and / or prevention of sexually transmitted diseases with biomimetic functions.

[0015] As can be seen from the above solutions, this application provides a flexible biomimetic polyurethane condom, its preparation method, and its application. This flexible biomimetic polyurethane condom, its preparation method, and its application have the following beneficial effects: 1. By constructing a slip ring crosslinking structure using polyrotaxane polyol and introducing an auxiliary chain extender containing light / mechanical responsive groups to form a sacrificial bond network, the base film layer has a soft feel in the low strain region and provides reliable mechanical properties through strain hardening in the high strain region. 2. The α-cyclodextrin of polyrotaxane polyol slides along the axial chain of polyethylene glycol to generate a pulley effect during stretching in application, which uniformly disperses stress between molecular chains and avoids local stress concentration that leads to a decrease in integrity; and the auxiliary chain extender containing spiropyran or diarylethylene structure acts as a light / mechanical response sacrificial bond to open the ring and dissipate mechanical energy under stress, so that the auxiliary chain extender and polyrotaxane polyol synergistically improve the soft touch of the base film in the low strain region and the toughness in the high strain region; 3. By forming a reversible ionic crosslinking network with the carboxyl groups of the hydrophilic chain extender through polyvalent metal ions, the density and interfacial bonding strength of the hydrophilic dense surface layer are enhanced. Since the hydrophilic dense surface layer has polyethylene oxide segments and hyaluronic acid components, a stable hydration lubricating layer will be formed, thereby reducing frictional resistance and improving fit and tactile realism. Detailed Implementation

[0016] The technical solutions described below in conjunction with the embodiments of this application will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0017] In the embodiments of this application, the polyisocyanate may be selected from at least one of hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate. The polymeric polyol is a polycaprolactone-polytetrahydrofuran random copolymer polyol, wherein the molar ratio of polycaprolactone segments to polytetrahydrofuran segments is (6-8):(2-4), and the number average molecular weight is 1000-3000. The hydrophilic chain extender is dimethylolpropionic acid and / or dimethylolbutyric acid. It should be noted that, in the specific embodiments of this application, the polyisocyanate is hexamethylene diisocyanate. The polymeric polyol is a polycaprolactone-polytetrahydrofuran random copolymer polyol, wherein the molar ratio of polycaprolactone segments to polytetrahydrofuran segments is 7:3, and the number average molecular weight is 2200. The hydrophilic chain extender is dimethylolpropionic acid.

[0018] The following is a detailed description of a flexible biomimetic polyurethane condom, its preparation method, and its application, based on this application.

[0019] A method for preparing a flexible biomimetic polyurethane condom includes the following steps: Step 1, Prepolymerization reaction: Polyisocyanate, polyrotaxane polyol, and polymer polyol are prepolymerized at 70-90℃ for 2-4 hours to obtain NCO-terminated prepolymer.

[0020] Polyrotaxane polyol is obtained by inclusion reaction of polyethylene glycol aqueous solution with α-cyclodextrin and end-capping with a capping agent. The concentration of the polyethylene glycol aqueous solution is 5-15 wt%. The molar ratio of α-cyclodextrin to polyethylene glycol is (5-30):1. The inclusion reaction temperature is 60-80℃, and the inclusion time is 2-6 h. The molar ratio of the capping agent to the terminal hydroxyl groups of polyethylene glycol is (2-3):1, and the end-capping reaction temperature is controlled at 25-50℃, and the end-capping reaction time is 12-24 h. The capping agent is at least one of adamantane, triphenylmethyl isocyanate, or pyrene isocyanate. A catalyst, accounting for 0.01-0.1% of the total mass, is added to the prepolymerization reaction. The catalyst is an organobismuth catalyst or an organotin catalyst.

[0021] Step 2, chain extension and dispersion: Take the NCO-terminated prepolymer and add a hydrophilic chain extender and an auxiliary chain extender. Control the temperature at 50-70℃ and allow the chain extension reaction to proceed for 0.5-1.5 hours. After neutralization by adding triethylamine and / or triethanolamine, control the degree of neutralization to 70-100%. Then add water for emulsification and dispersion to obtain a waterborne polyurethane latex with a solid content of 25-45%.

[0022] Step 3, Impregnation molding: Immerse the mold in water-based polyurethane latex, and after multiple impregnations, interlayer drying and curing, a base film layer is formed.

[0023] In the impregnation process, the impregnation speed is controlled at 1-5 mm / s, the single impregnation time is 10-60 s, and 2-5 impregnations are performed. In the interlayer drying process, the temperature is controlled at 40-70℃, and the time is 3-10 min. In the curing process, the temperature is controlled at 70-90℃, and the time is 10-30 min.

[0024] At the same time, the base film layer is surface treated to obtain a dense film layer, and the dense film layer is ion crosslinked to obtain a composite base film layer.

[0025] The surface treatment involves immersing the base film layer in a surface slurry and then drying it to form a hydrophilic and dense surface layer. The immersion rate for the surface treatment is 0.5-3 mm / s, and the immersion time is 5-30 s. The drying temperature is 40-60℃, the drying time is 3-8 min, and the thickness of the hydrophilic and dense surface layer is controlled to be 2-10 μm. The surface slurry has a solid content of 10-30% and includes 5-20% by mass of isocyanate-terminated prepolymer, 0.5-3% of a moisturizing and lubricating component, and the balance being hydrophilic segments. The isocyanate-terminated prepolymer is prepared from at least one of polyisocyanate and polyether polyol or polyester polyol, with an NCO content of 3-12 wt% and a number average molecular weight of 500-3000. The moisturizing and lubricating component is at least one of hyaluronic acid, polyethylene glycol, and chitosan. The hydrophilic segments are polyoxyethylene segments, with a number average molecular weight of 400-2000.

[0026] Ion crosslinking treatment involves immersing a dense film layer in a crosslinking solution containing polyvalent metal ions for crosslinking impregnation. Polyvalent metal ions include Ca... 2+ Zn 2+ Or Al 3+ At least one of the following. The crosslinking solution is at least one of calcium chloride aqueous solution, zinc acetate aqueous solution, or aluminum chloride aqueous solution. The mass concentration of the crosslinking solution is controlled at 1-10%, the crosslinking immersion time is 30-300s, and the immersion temperature is 20-40℃.

[0027] Step 4, Post-processing: After demolding and cleaning, the finished flexible bionic polyurethane condom is obtained.

[0028] The cleaning process involves immersing the condom in deionized water at 20-30℃ for 5-15 minutes, followed by adding 0.5-3.0g of water-soluble lubricant per condom to obtain the finished flexible biomimetic polyurethane condom. The water-soluble lubricant is at least one of hyaluronic acid aqueous solution, polyethylene glycol aqueous solution, and glycerin aqueous solution. The hyaluronic acid aqueous solution contains 0.1-1% hyaluronic acid by mass, the polyethylene glycol aqueous solution contains 5-30% polyethylene glycol by mass, and the glycerin aqueous solution contains 10-50% glycerin by mass.

[0029] in: Based on the molar amount of NCO, the amount of each component is the percentage of the number of moles of active hydrogen groups (OH) provided by that component relative to the total moles of NCO. The amount of polyrotaxane polyol is 10-35%, and the amount of polymer polyol is 20-50%. The amount of hydrophilic chain extender is 5-15%, and the amount of auxiliary chain extender is 1-8%.

[0030] The auxiliary chain extender is a chain extender containing a spiropyran structure or a photo / mechanical responsive molecule containing a diarylethylene structure.

[0031] A flexible biomimetic polyurethane condom is prepared using the method described above. The flexible biomimetic polyurethane condom includes a base film layer and a hydrophilic dense surface layer disposed on the outer surface of the base film layer.

[0032] An application of a flexible biomimetic polyurethane condom includes using a flexible biomimetic polyurethane condom as described above and applying it for contraception and / or prevention of sexually transmitted diseases with biomimetic functions. Example 1

[0033] A method for preparing a flexible biomimetic polyurethane condom includes the following steps: Step 1, Prepolymerization reaction: Polyisocyanate, polyrotaxane polyol, and polymer polyol are prepolymerized at 75°C for 3 hours to obtain NCO-terminated prepolymer.

[0034] Polyrotaxane polyol was obtained by inclusion reaction of polyethylene glycol aqueous solution with α-cyclodextrin and then end-capping with a capping agent. The concentration of the polyethylene glycol aqueous solution was 8 wt%. The molar ratio of α-cyclodextrin to polyethylene glycol was 10:1. The inclusion reaction temperature was 65℃, and the inclusion time was 3 h. The molar ratio of the capping agent to the terminal hydroxyl groups of polyethylene glycol was 2.2:1, and the end-capping reaction temperature was controlled at 30℃, and the end-capping reaction time was 18 h. The capping agent was adamantaneamine. A catalyst, an organobismuth catalyst, was added at 0.03% of the total mass during the prepolymerization reaction.

[0035] Step 2, chain extension and dispersion: Take the NCO-terminated prepolymer and add a hydrophilic chain extender and an auxiliary chain extender. Control the temperature at 55℃ and react for 1 hour. After adding triethylamine to neutralize, control the degree of neutralization to 80%. Then add water to emulsify and disperse to obtain a waterborne polyurethane latex with a solid content of 30%.

[0036] Step 3, Impregnation molding: The mold is immersed in water-based polyurethane latex, and after multiple impregnations, interlayer drying and curing, a base film layer is formed.

[0037] In the impregnation process, the impregnation speed was controlled at 2 mm / s, the single impregnation time was 30 s, and the impregnation was repeated 3 times. In the interlayer drying process, the temperature was controlled at 50℃ and the time was 5 min. In the curing process, the temperature was controlled at 75℃ and the time was 20 min.

[0038] At the same time, the base film layer is treated with a surface layer to obtain a dense film layer, and the dense film layer is subjected to ion crosslinking treatment to obtain a composite base film layer.

[0039] The surface treatment involves immersing the base film layer in a surface slurry and then drying it to form a hydrophilic and dense surface layer. The immersion speed for the surface treatment is 1.5 mm / s, and the immersion time is 15 s. The drying temperature is 50°C, the drying time is 5 min, and the thickness of the hydrophilic and dense surface layer is controlled to be 5 μm. The surface slurry has a solid content of 20% and includes 10% isocyanate-terminated prepolymer, 1.5% moisturizing and lubricating component, and the balance being hydrophilic segments. The isocyanate-terminated prepolymer is prepared from polyisocyanate and polyether polyol, with an NCO content of 6 wt% and a number average molecular weight of 1500. The moisturizing and lubricating component is hyaluronic acid. The hydrophilic segments are polyethylene oxide segments with a number average molecular weight of 800.

[0040] Ion crosslinking treatment involves immersing the dense film layer in a crosslinking solution containing polyvalent metal ions for crosslinking impregnation. The polyvalent metal ion is Ca. 2+ The crosslinking solution was an aqueous solution of calcium chloride. The mass concentration of the crosslinking solution was controlled at 3%, the crosslinking immersion time was 120 seconds, and the immersion temperature was 30℃.

[0041] Step 4, Post-processing: After demolding and cleaning, the finished flexible biomimetic polyurethane condom is obtained.

[0042] The cleaning process involves immersing the condom in deionized water at 25°C for 10 minutes, followed by adding 1.5g of water-soluble lubricant per condom to obtain the finished flexible biomimetic polyurethane condom. The water-soluble lubricant is an aqueous solution of hyaluronic acid, with a mass fraction of 0.5% hyaluronic acid.

[0043] in: Based on the molar amount of NCO, the amount of polyrotaxane polyol is 18%, and the amount of polymer polyol is 40%. The amount of hydrophilic chain extender is 8%, and the amount of auxiliary chain extender is 3%. The auxiliary chain extender is a chain extender containing a spiropyran structure. Example 2

[0044] A method for preparing a flexible biomimetic polyurethane condom includes the following steps: Step 1, Prepolymerization reaction: Polyisocyanate, polyrotaxane polyol, and polymer polyol are prepolymerized at 80°C for 3 hours to obtain NCO-terminated prepolymer.

[0045] Polyrotaxane polyol was obtained by inclusion reaction of polyethylene glycol aqueous solution with α-cyclodextrin and then end-capping with a capping agent. The concentration of the polyethylene glycol aqueous solution was 10 wt%. The molar ratio of α-cyclodextrin to polyethylene glycol was 15:1. The inclusion reaction temperature was 70℃, and the inclusion time was 4 h. The molar ratio of the capping agent to the terminal hydroxyl groups of polyethylene glycol was 2.5:1, and the end-capping reaction temperature was controlled at 35℃, and the end-capping reaction time was 18 h. The capping agent was triphenylmethyl isocyanate. A catalyst, an organotin catalyst, was added at 0.05% of the total mass during the prepolymerization reaction.

[0046] Step 2, Chain Extension and Dispersion: Take the NCO-terminated prepolymer and add a hydrophilic chain extender and an auxiliary chain extender. Control the temperature at 60℃ and react for 1 hour. After adding triethylamine and triethanolamine to neutralize, control the degree of neutralization to 90%. Then add water to emulsify and disperse to obtain a waterborne polyurethane latex with a solid content of 35%.

[0047] Step 3, Impregnation molding: The mold is immersed in water-based polyurethane latex, and after multiple impregnations, interlayer drying and curing, a base film layer is formed.

[0048] In the impregnation process, the impregnation speed was controlled at 3 mm / s, the single impregnation time was 40 s, and the impregnation was repeated 3 times. In the interlayer drying process, the temperature was controlled at 55℃ and the time was 6 min. In the curing process, the temperature was controlled at 80℃ and the time was 20 min.

[0049] At the same time, the base film layer is treated with a surface layer to obtain a dense film layer, and the dense film layer is subjected to ion crosslinking treatment to obtain a composite base film layer.

[0050] The surface treatment involves immersing the base film layer in a surface slurry and drying it to form a hydrophilic and dense surface layer. The immersion speed is 2 mm / s, and the immersion time is 20 s. The drying temperature is 50℃, the drying time is 5 min, and the thickness of the hydrophilic and dense surface layer is controlled to be 6 μm. The surface slurry has a solid content of 25% and includes 12% isocyanate-terminated prepolymer, 2% moisturizing and lubricating components, and the balance being hydrophilic segments. The isocyanate-terminated prepolymer is prepared from polyisocyanate, polyether polyol, and polyester polyol, with an NCO content of 8 wt% and a number average molecular weight of 2000. The moisturizing and lubricating components are hyaluronic acid and polyethylene glycol. The hydrophilic segments are polyethylene oxide segments with a number average molecular weight of 1000.

[0051] Ion crosslinking treatment involves immersing the dense film layer in a crosslinking solution containing polyvalent metal ions for crosslinking impregnation. The polyvalent metal ion is Zn. 2+ The crosslinking solution was an aqueous solution of zinc acetate. The mass concentration of the crosslinking solution was controlled at 5%, the crosslinking immersion time was 180 seconds, and the immersion temperature was 30°C.

[0052] Step 4, Post-processing: After demolding and cleaning, the finished flexible biomimetic polyurethane condom is obtained.

[0053] The cleaning process involves immersing the condom in deionized water at 25°C for 10 minutes, followed by adding 2.0 g of water-soluble lubricant per condom to obtain the finished flexible biomimetic polyurethane condom. The water-soluble lubricant is a polyethylene glycol aqueous solution. The mass fraction of polyethylene glycol in the polyethylene glycol aqueous solution is 15%.

[0054] in: Based on the molar amount of NCO, the amount of polyrotaxane polyol is 25%, and the amount of polymer polyol is 35%. The amount of hydrophilic chain extender is 10%, and the amount of auxiliary chain extender is 5%.

[0055] The auxiliary chain extender is a photo / mechanical responsive molecule containing a diarylethene structure. Example 3

[0056] A method for preparing a flexible biomimetic polyurethane condom includes the following steps: Step 1, Prepolymerization reaction: Polyisocyanate, polyrotaxane polyol, and polymer polyol are prepolymerized at 85°C for 3.5 hours to obtain NCO-terminated prepolymer.

[0057] Polyrotaxane polyol was obtained by inclusion reaction of polyethylene glycol aqueous solution with α-cyclodextrin and then end-capping with a capping agent. The concentration of the polyethylene glycol aqueous solution was 12 wt%. The molar ratio of α-cyclodextrin to polyethylene glycol was 20:1. The inclusion reaction temperature was 75℃, and the inclusion time was 5 h. The molar ratio of the capping agent to the terminal hydroxyl groups of polyethylene glycol was 2.8:1, and the end-capping reaction temperature was controlled at 40℃, and the end-capping reaction time was 20 h. The capping agent was pyrene isocyanate. A catalyst, an organobismuth catalyst, was added at 0.08% by mass during the prepolymerization reaction.

[0058] Step 2, Chain Extension and Dispersion: Take the NCO-terminated prepolymer and add a hydrophilic chain extender and an auxiliary chain extender. Control the temperature at 65℃ and perform a chain extension reaction for 1.2 hours. After adding triethanolamine to neutralize and controlling the degree of neutralization to 95%, add water for emulsification and dispersion to obtain a waterborne polyurethane latex with a solid content of 40%.

[0059] Step 3, Impregnation molding: The mold is immersed in water-based polyurethane latex, and after multiple impregnations, interlayer drying and curing, a base film layer is formed.

[0060] In the impregnation process, the impregnation speed was controlled at 4 mm / s, the single impregnation time was 50 s, and 4 impregnations were performed. In the interlayer drying process, the temperature was controlled at 60℃ and the time was 8 min. In the curing process, the temperature was controlled at 85℃ and the time was 25 min.

[0061] At the same time, the base film layer is treated with a surface layer to obtain a dense film layer, and the dense film layer is subjected to ion crosslinking treatment to obtain a composite base film layer.

[0062] The surface treatment involves immersing the base film layer in a surface slurry and then drying it to form a hydrophilic and dense surface layer. The immersion rate for the surface treatment is 2.5 mm / s, and the immersion time is 25 s. The drying temperature is 55°C, the drying time is 6 min, and the thickness of the hydrophilic and dense surface layer is controlled to be 8 μm. The surface slurry has a solid content of 28% and includes 18% isocyanate-terminated prepolymer, 2.5% moisturizing and lubricating components, and the balance being hydrophilic segments. The isocyanate-terminated prepolymer is prepared from polyisocyanate and polyester polyol, with an NCO content of 10 wt% and a number average molecular weight of 2500. The moisturizing and lubricating components are chitosan and polyethylene glycol. The hydrophilic segments are polyethylene oxide segments with a number average molecular weight of 1500.

[0063] Ion crosslinking treatment involves immersing the dense film layer in a crosslinking solution containing polyvalent metal ions for crosslinking impregnation. The polyvalent metal ions are Al... 3+ The crosslinking solution was an aqueous solution of aluminum chloride. The mass concentration of the crosslinking solution was controlled at 8%, the crosslinking immersion time was 240 seconds, and the immersion temperature was 35℃.

[0064] Step 4, Post-processing: After demolding and cleaning, the finished flexible biomimetic polyurethane condom is obtained.

[0065] The cleaning process involved immersing the condom in deionized water at 28°C for 12 minutes, followed by adding 2.5g of water-soluble lubricant per condom to obtain the finished flexible biomimetic polyurethane condom. The water-soluble lubricant was an aqueous glycerin solution with a glycerin mass fraction of 30%.

[0066] in: Based on the molar amount of NCO, the amount of polyrotaxane polyol is 30%, and the amount of polymer polyol is 45%. The amount of hydrophilic chain extender is 12%, and the amount of auxiliary chain extender is 6%.

[0067] The auxiliary chain extender is a chain extender containing a spiropyran structure.

[0068] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that in Comparative Example 1, an equimolar amount of polymer polyol was used instead of polyrotaxane polyol.

[0069] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that in Comparative Example 2, an equimolar amount of hydrophilic chain extender is used instead of the auxiliary chain extender.

[0070] Performance testing: 1. Test the burst volume, burst pressure, breaking force and elongation at break according to GB 7544-2019.

[0071] 2. The coefficient of kinetic friction shall be tested in accordance with GB / T 10006-2021, and the water contact angle shall be tested in accordance with GB / T 30693-2014.

[0072] 3. Tear strength shall be tested in accordance with GB / T 529-2008, and elastic recovery rate shall be tested in accordance with GB / T 528-2009.

[0073] 4. The color difference ΔE was tested according to GB / T 7921-2008, using a wavelength of 365nm and a power density of 5mW / cm². 2 After irradiating the sample surface with ultraviolet light for 60 seconds, the L*, a*, and b* values ​​before and after irradiation were measured using a colorimeter, and ΔE was calculated.

[0074] 5. Test Shore A hardness according to GB / T 531.1-2008.

[0075] The performance test results are shown in Table 1 below.

[0076] Explosion volume (L) 24.5 28.3 32.6 18.2 21.5 Burst pressure (kPa) 1.35 1.52 1.68 1.05 1.18 Breaking force (N) 36.8 42.5 48.2 28.5 32 Elongation at break (%) 685 738 792 485 568 Shore A hardness 38 32 28 52 45 coefficient of kinetic friction 0.065 0.048 0.038 0.095 0.112 Water contact angle (°) 42.5 35.8 28.6 68.3 62.5 Tear strength (kN / m) 28.5 32.8 36.2 18.5 22 Elastic recovery rate (%) 92.5 95.2 96.8 82.3 88.5 Color difference ΔE 18.5 22.3 19.8 0.5 0.8 As shown in Table 1 above, the burst volume, burst pressure, tensile force, and elongation at break of Examples 1 to 3 of this application all meet the mandatory requirements of GB 7544-2019. Their performance test results are significantly better than Comparative Examples 1 and 2. The key reason is that Comparative Example 1, due to the absence of polyrotaxane polyol, lacks the stress dispersion effect of α-cyclodextrin sliding along the polyethylene glycol chain, resulting in a Shore A hardness of 52, a decrease in elongation at break to 485%, a tear strength of 18.5 kN / m, and an elastic recovery rate of 82.3%. Comparative Example 2, due to the absence of an auxiliary chain extender, suffers from a decrease in the integrity of the crosslinked network. Although its mechanical properties are higher than Comparative Example 1, there is a significant difference compared to Example 2, and its color difference ΔE is low, thus lacking light / force response functionality.

[0077] In Examples 1 to 3, as the amount of polyrotaxane polyol increased, the valence state of the ion-crosslinked metal ions changed from Ca... 2+ Increment to Al 3+ The optimization and improvement of the hydrophilic and dense surface components will enable the preparation of flexible biomimetic polyurethane condoms. The flexibility, elastic recovery rate, tear strength, and surface hydrophilicity were all consistently improved. This shows that the synergistic effect of polyrotaxane slip ring, coordination crosslinking of multivalent metal ions, and hydrophilic dense surface layer significantly improved the flexibility and strength of the flexible biomimetic polyurethane condom, and significantly optimized and reduced the coefficient of friction.

[0078] In summary, this application provides a flexible biomimetic polyurethane condom, its preparation method, and its application. This flexible biomimetic polyurethane condom utilizes a polyrotaxane polyol to construct a slip-ring crosslinked structure and introduces an auxiliary chain extender containing light / mechanical responsive groups to form a sacrificial bond network. This results in a base film layer that exhibits a soft feel in the low-strain region and provides reliable mechanical properties through strain hardening in the high-strain region. The preparation method of this flexible biomimetic polyurethane condom utilizes the formation of a reversible ionic crosslinked network between polyvalent metal ions and the carboxyl groups of a hydrophilic chain extender, thereby enhancing the density and interfacial bonding strength of the hydrophilic dense surface layer. Because the hydrophilic dense surface layer contains polyethylene oxide segments and hyaluronic acid components, a stable hydrated lubricating layer is formed, achieving the effects of reducing frictional resistance, improving fit, and enhancing tactile realism.

[0079] Meanwhile, the flexible biomimetic polyurethane condom utilizes the α-cyclodextrin of polyrotaxane polyol to slide along the polyethylene glycol axial chain, creating a pulley effect during stretching in application. This uniformly disperses stress between molecular chains, preventing localized stress concentration that could lead to a decrease in integrity. Furthermore, the auxiliary chain extender containing spiropyran or diarylethylene structures acts as a light / mechanical response sacrificial bond, opening the ring and dissipating mechanical energy under stress. This allows the auxiliary chain extender and polyrotaxane polyol to synergistically enhance the soft feel of the base film in the low-strain region and its toughness in the high-strain region.

[0080] The terms “first,” “second,” “third,” “fourth,” etc., used in this application (if applicable) are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments described herein can be implemented in orders other than those described herein. Furthermore, the terms “comprising” and “having,” and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, or apparatus that includes a series of steps or units is not necessarily limited to those explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, or apparatus.

[0081] It should be noted that the use of terms such as "first" and "second" in this application is for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of those features. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. If the combination of technical solutions is contradictory or impossible to implement, such a combination of technical solutions should be considered non-existent and not within the scope of protection claimed in this application.

[0082] This document uses specific examples to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A method for preparing a flexible biomimetic polyurethane condom, characterized in that, Includes the following steps: Step 1, Prepolymerization reaction: Polyisocyanate, polyrotaxane polyol, and polymer polyol are prepolymerized at 70-90℃ for 2-4 hours to obtain NCO-terminated prepolymer; Step 2, chain extension and dispersion: Take the NCO-terminated prepolymer and add a hydrophilic chain extender and an auxiliary chain extender. Control the temperature at 50-70℃ and carry out the chain extension reaction for 0.5-1.5 hours. Then add water to emulsify and disperse to obtain waterborne polyurethane latex. Step 3, Impregnation molding: The mold is immersed in water-based polyurethane latex, and after multiple impregnations, interlayer drying and curing, a base film layer is formed; Step 4, Post-processing: After demolding and cleaning, the finished flexible bionic polyurethane condom is obtained. in: Based on the molar amount of NCO, the amount of the polyrotaxane polyol is 10-35%, the amount of the polymer polyol is 20-50%, the amount of the hydrophilic chain extender is 5-15%, and the amount of the auxiliary chain extender is 1-8%. The hydrophilic chain extender is a hydrophilic chain extender containing a carboxyl group; the auxiliary chain extender is an auxiliary chain extender containing a photo / mechanical responsive group.

2. The method for preparing a flexible biomimetic polyurethane condom according to claim 1, characterized in that: In step 1, the polyrotaxane polyol is obtained by inclusion reaction of polyethylene glycol aqueous solution and α-cyclodextrin followed by end-capping with an end-capping agent; the concentration of the polyethylene glycol aqueous solution is 5-15 wt%; the molar ratio of α-cyclodextrin to polyethylene glycol is (5-30):1; the temperature of the inclusion reaction is 60-80℃, and the inclusion time is 2-6 h; the molar ratio of the end-capping agent to the terminal hydroxyl group of the polyethylene glycol is (2-3):1, and the end-capping reaction temperature is controlled at 25-50℃, and the end-capping reaction time is 12-24 h; the end-capping agent is at least one of adamantane, triphenylmethyl isocyanate, or pyrene isocyanate; the prepolymerization reaction is added with a catalyst accounting for 0.01-0.1% of the total mass, and the catalyst is an organobismuth catalyst or an organotin catalyst.

3. The method for preparing a flexible biomimetic polyurethane condom according to claim 1, characterized in that: In step 2, triethylamine and / or triethanolamine are added for neutralization before emulsification and dispersion, and the degree of neutralization is controlled to be 70-100%; the solid content of the waterborne polyurethane latex is 25-45%.

4. The method for preparing a flexible biomimetic polyurethane condom according to claim 1, characterized in that: In step 3, the impregnation speed is 1-5 mm / s, the single impregnation time is 10-60 s, and the impregnation is repeated 2-5 times; the interlayer drying temperature is 40-70℃, and the time is 3-10 min; the curing temperature is 70-90℃, and the time is 10-30 min.

5. The method for preparing a flexible biomimetic polyurethane condom according to claim 1, characterized in that: In step 3, the base film layer undergoes surface treatment to obtain a dense film layer; the surface treatment involves immersing the base film layer in a surface slurry and drying it to form a hydrophilic and dense surface layer; the immersion rate of the surface treatment is 0.5-3 mm / s, and the immersion time is 5-30 s; the drying temperature is 40-60℃, and the drying time is 3-8 min; and the thickness of the hydrophilic and dense surface layer is controlled to be 2-10 μm.

6. The method for preparing a flexible biomimetic polyurethane condom according to claim 5, characterized in that: The surface slurry has a solid content of 10-30% and includes 5-20% by mass of isocyanate-terminated prepolymer, 0.5-3% of moisturizing and lubricating components, and the balance being hydrophilic segments; the isocyanate-terminated prepolymer is prepared from at least one of polyisocyanate and polyether polyol and polyester polyol, and has an NCO content of 3-12 wt% and a number average molecular weight of 500-3000; the moisturizing and lubricating components are at least one of hyaluronic acid, polyethylene glycol and chitosan; the hydrophilic segments are polyethylene oxide segments and have a number average molecular weight of 400-2000.

7. The method for preparing a flexible biomimetic polyurethane condom according to claim 5, characterized in that: The dense film layer is subjected to ion crosslinking treatment to obtain a composite base film layer; the ion crosslinking treatment includes immersing the dense film layer in a crosslinking solution containing multivalent metal ions for crosslinking impregnation treatment; the multivalent metal ions include Ca 2+ Zn 2+ Or Al 3+ At least one of the following: the crosslinking solution is at least one of calcium chloride aqueous solution, zinc acetate aqueous solution or aluminum chloride aqueous solution; the mass concentration of the crosslinking solution is 1-10%, and the crosslinking immersion treatment time is controlled to be 30-300s, and the immersion temperature is 20-40℃.

8. The method for preparing a flexible biomimetic polyurethane condom according to claim 1, characterized in that: The auxiliary chain extender is a chain extender containing a spiropyran structure or a photo / mechanical responsive molecule containing a diarylethylene structure.

9. A flexible biomimetic polyurethane condom, characterized in that: The flexible biomimetic polyurethane condom is prepared by the preparation method of any one of claims 1-8, wherein the flexible biomimetic polyurethane condom includes a base film layer and a hydrophilic dense surface layer disposed on the outer surface of the base film layer.

10. The application of a flexible biomimetic polyurethane condom, characterized in that: This includes using a flexible biomimetic polyurethane condom as described in claim 9, and applying it to contraception and / or prevention of sexually transmitted diseases with biomimetic functions.